Agile Readiness Assessment of IT Audit Function at Indonesia’s State-Owned Bank - Dedi Kurniawan; Raharjo, Teguh; Nur Fitriani, Anita (The Indonesian Journal of Computer Science, 2024)
Recently, there has been increased interest in using Agile methodologies in auditing to improve efficiency and adaptability. This study examines whether Bank XYZ in Indonesia is ready to adopt Agile for IT auditing, marking a first for the country's banks. The need for Agile is driven by a significant reduction in audit staff, increased demands from management, and higher fraud risks, all of which call for a more effective and responsive audit process. The research employed both surveys based on the CA Agile Framework and qualitative analysis. It found that Bank XYZ is moderately ready to adopt Agile, showing strengths in commitment to user research, organizational culture, and training support. However, challenges such as utilizing past Agile experiences and enhancing governance must be addressed. The study recommends a gradual adoption of Agile, focusing on building a supportive Agile culture, enhancing training for auditors, and improving governance structures. This step-by-step approach will help Bank XYZ effectively integrate Agile into its IT auditing practices to better meet management's expectations for more business-focused auditing.